Technogenic transformation of steppe soils of the European part of Russia under conditions of hydrocarbon pollution - S. A. Sidorenko (Наука. Инновации. Технологии)
The object of the study is the soils of the Orenburg region, Buzuluk district, contaminated with pollutants. The aim of the study is to identify patterns of accumulation of heavy metals in southern chernozems that have been subjected to hydrogen pollution and the studied conglomerate by pollutants of the European part of the steppes of Russia. As well as the establishment of a set of factors and confirmation of their influence on the stability of landscapes in conditions of soil degradation and further formation of geochemical barriers formed by pollutants. The materials and methods of research are the literature of leading Russian specialists studying this issue, as well as regulatory and legal documentation: GOST standards, SanPiNs, Resolutions of the Government of the Russian Federation. Cartographic and graphic materials have been built that display sampling points, the content and dependence of elements on pollutants. A field survey (reconnaissance of the area) was conducted in the conditions of eluvial formation of soil and soil-forming accumulation, against the background of changes in the processes of formation of geochemical chains. Soil samples were taken from the site, and a syntaxoid analysis was performed. The total value of the maximum permissible concentrations of pollutants in the soils of the studied area within the boundaries of the administrative region of three oil fields has been determined. According to the results of the study, a pattern of accumulation of heavy metals from the area of the geochemical barrier formed by pollution with petroleum products was revealed. The perspective of the development of the influence of accumulations of pollutants on the transformation of the natural landscape is visualized. In areas contaminated with pollutants, it is necessary to carry out reclamation works: technical and biological stages, in compliance with environmental protection.